Impact of Coping Capacity Skills on Resilience of Disaster Affected Communities in United Arab Emirates - Almazrouei, Ahmed Shames Rashed Saif; Mat Radzuan, Indera Syahrul (Journal of Social Transformation and Regional Development, 2026)
The primary goal of this study was to assess the impact of coping capacity skills on the resilience of disaster-affected communities in the United Arab Emirates (UAE). Specifically, the study examines how skills such as preparedness, emergency response, psychological coping, adaptive capacity, social capital, and access to information contribute to enhancing community resilience. A quantitative methodology was employed, using data from 277 respondents drawn from various disaster-affected communities in the country. Peason’s Correlation and Multiple linear regression analysis was conducted to determine the influence of these coping capacity skills on overall resilience, while controlling for income level as a confounding variable. The results indicated that all examined coping capacity skills positively and significantly contributed to overall resilience (R² = 0.65). Particularly, access to information (β = 0.26, p < 0.05) and adaptive capacity (β = 0.28, p < 0.01) emerged as the most impactful predictors of resilience, followed by social capital (β = 0.22, p < 0.01). Preparedness (β = 0.17, p < 0.01), emergency response skills (β = 0.13, p < 0.01), and psychological coping (β = 0.16, p < 0.05) also showed significant positive effects on resilience. Income level was found to be a significant confounding factor (β = 0.12, p < 0.01), suggesting that socio-economic resources play a crucial role in disaster recovery. The study underscores the importance of a comprehensive approach to building disaster resilience that includes strengthening multiple coping capacity skills. These findings provide actionable insights for policymakers and disaster management professionals aiming to enhance the resilience of communities in the UAE.